PENENTUAN TINGKAT AKTIFITAS CHOLINESTERASE DARAH YANG KEBIASAAN MENGGUNAKAN OBAT ANTINYAMUK BAKAR PADA PENDUDUK KELURAHAN JATI PADANG - Elmatris Sy; Yustini Alioes; Miftah Irramah (Jurnal Riset Kimia, 2011)
ABSTRACTThis study aims to determine the level of blood cholinesterase activity using a drug habit antinyamuk fuel (OANB), in Kelurahan Jati Padang and analyzed at the Laboratory of Biochemistry at the Faculty of Medicine in April-November 2010. The population is all residents Jati Padang village. The sample is using drugs antinyamuk fuel that is 30 people with sampling techniques eccidental sampling, as control is a resident who does not use drugs antinyamuk (Joan). The results showed: the population of 74 people who came, in getting 30 people to use OANB, 39 people who do not use OANB (liquid and lotion), 5 people who did not use Joan (as control). The average level of blood cholinesterase activity using OANB is 7294.79 u / l, and that does not use Joan is 7645.97 u / l. In conclusion, the average level of blood cholinesterase activity in the population there is a tendency Kelurahan Jati Padang cholinesterase activity levels decreased when compared to controls. Decrease in the average value of cholinesterase activity and a decrease of 5% is still within normal limits. Keywords: drug antinyamuk fuel, cholinesterase